Seroprevalence of antibodies against varicella zoster virus across all age groups during the post-COVID-19 pandemic period in Chonburi Province, Thailand - Thanunrat Thongmee; Jira Chansaenroj; Sirapa Klinfueng; Ratchadawan Aeemjinda; Nasamon Wanlapakorn; Yong Poovorawan (Taylor & Francis Group, 2024)
As of 2024, Thailand has not incorporated the varicella-zoster virus (VZV) vaccine into the Expanded Program on Immunization (EPI). This study aimed to evaluate VZV seroprevalence across all age groups in Chonburi Province, Thailand, during the post-COVID-19 era, and to support the development of a vaccination plan against VZV. A total of 950 participants were enrolled from October 2022 to January 2023. VZV antibody levels were measured using ELISA kits (EUROIMMUN, Lübeck, Germany), with seropositivity set at ≥110 IU/L. The overall VZV seropositivity rate was 64.8%, similar to rates in 1994 and 2014. However, seropositivity rates for the 5-9, 10-14, and 15-19 age groups were significantly higher in the 1994 study, and for the 10-14 and 15-19 age groups in the 2014 study, indicating a declining trend among young Thai individuals. The seropositivity rate increased with age, with a seroprevalence exceeding 80% in individuals aged 30 years and older. Our study found a significant association between the history of varicella and seropositivity. Thus, a positive history may indicate immunity. In conclusion, a significant portion of Thai adolescents are still vulnerable to varicella, highlighting the crucial role of vaccination in averting serious illness.